Analisa Pengaruh Maintenance Cylinder Block Terhadap Efisiensi Bahan Bakar Mesin Speedboat Mercury 450 Racing V8 - Purnomo, Seno Aji; Adiwibowo, Priyo Heru (TURBO [Tulisan Riset Berbasis Online], 2025)
This study aims to evaluate how the condition of the cylinder block affects the fuel efficiency of a Mercury 450 Racing V8 speedboat engine. As a vital component in the engine, the cylinder block is responsible for housing and supporting the cylinders, where the combustion process takes place. Damage to the cylinder block, such as cracks, corrosion, or wear, can lead to decreased compression pressure and gas leakage, resulting in decreased combustion efficiency and increased fuel consumption. This study used an experimental approach to assess the effect of different levels of cylinder block damage on engine fuel efficiency. The results showed that the condition of the cylinder block significantly affects fuel efficiency, with damaged cylinder blocks drastically reducing engine efficiency. These findings highlight the importance of regular maintenance and repair of the cylinder block to maintain optimal fuel efficiency and improve speedboat engine performance. The repair of the cylinder block gave an improved fuel consumption efficiency of 22.22% meaning the engine became more efficient in using fuel after the repair of the problem of sticking shells and oil leakage.